AKUNTABILITAS DAN GOOD CORPORATE GOVERNANCE PADA PELAYANAN PUBLIK DI BIDANG PENDIDIKAN - Puji - Nuryati (Universitas Slamet Riyadi, 2014)
ABSTRACT Education is one of public services. Public service education is very important thing for societ, in improving its quality, improvement quality of teachers and staff of education, as well education service management which of high quality need good corporate governance (GCG). The application of good governance can improve good public service. In management of financial education should follow/submit accountability principle and transparency. Accountability in management of education is needed as a justifying from to wards financial. The usage and performance school organizer. The aims of this paper are providing description accountability application and good corporate governance to public service education or school. This submitted because in fact there are only some schools which are implementing accountability and good corporate governance rightly. The main principles which are underlied good school governance are (first) accounting, (second) transparancy, and (third) participation. School/ education institution is public which is societies are providing their faith in education case need apply good school governance (GCG) even though there is not universal good governance model for school. Keywords: Good school governance, accountability, good school governance.